Menuju Gereja Terjaring (Networked Chruch) - Gerardus Hadian Panamokta (P3TK, Sanata Dharma University, 2018)
The social operating system of the networked individualism invites the Church to reflect on the notion of communion of the networked Church. Through textual analysis from selected resources it is found that relationality aspect was celebrated and nurtured in the term of the networked individualism and the Church communion. Trinity which is relational being and human Christian anthropology which is relational embedded in networked individualism context. Networked Church provides theological arguments that the networked individualism develops the meaning of communion in the Church which is a new paradox of a back and forth online-offline relation.